Preventive Detention in Germany: An Overview and Empirical Data from Two Federal States. (14th May 2013) - Basdekis‐Jozsa, Raphaela; Mokros, Andreas; Vohs, Knut; Briken, Peer; Habermeyer, Elmar
Abstract : Eighty years ago, preventive detention for dangerous offenders was implemented in the German Penal Code (Section 66). In 2011, about 500 individuals were incarcerated under a preventive detention order in Germany. Through semi‐structured clinical interviews and/or collateral file review, the present investigators assessed the sociobiographic, criminological, and clinical characteristics of 58 men for whom preventive detention had been ordered in two German federal states. In addition, risk assessment instruments were administered. The majority of the inmates were sexual offenders. The main mental health problems were antisocial personality disorder (APD), substance abuse/disorder, and paraphilias. Most individuals had a history of poor socialization. Structured clinical judgment as well as actuarial risk assessment instruments identified all inmates as high‐risk offenders. Future development of preventive detention in Germany must emphasize treatment interventions. Given the life histories and the mental health problems of the detainees assessed in the present study, the implementation of effective treatment will prove difficult. Copyright © 2013 John Wiley & Sons, Ltd.